EFFECT OF DIFFERENT pH, TEMPERATURE AND SOLID MEDIA ON GROWTH OF PURPLE BLOTCH OF ONION CAUSED BY ALTERNARIA PORRI ELLIS - N. PRADNYARANI; M. S. KULKARNI (The Bioscan, 2015)
Purple blotch of onion caused by Alternaria porri is an important and destructive disease in onion growing areas of Karnataka. In vitro studies were conducted to know best solid media, temperature and pH on mycelial growth of Alternaria porri. Among the different solid media tested potato dextrose agar showed maximum mycelial growth (83.00 mm) with good sporulation. The maximum growth phase of the fungus was on 12 th day of incubation (207.00 mg). The optimum mycelial growth and sporulation was observed at temperature of 28 0 C and no growth and sporulation was observed at 15 0 C. The most suitable pH level for growth was ranged from 5.0 to 7.0.